Antimicrobial activity of emodin – secondary metabolites from Trichoderma against some human pathogenic bacteria in Wasit province, Iraq - Israa Jabbar Shamkhi; Alaa Mohisn AL Araji; Mohamed Mahmoud Hassan; Mohammed Fakhir Mohammed; Malik Mohammed (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the antibacterial activity of emodin isolated from trichoderma longibrachiatum against certain pathogens in patients with bacterial disease. Methods: The cross-sectional study was conducted at Al-Zahraa Teaching Hospital, Wassit, Iraq, from December 2021 to March 2022, and comprised tichoderma longibrachiatum taken from the Wasit University’s garden soil and were subjected to plate morphology, microscopic examination, and polymerase chain reaction-internal transcribed spacer testing. Emodin was extracted by ethyl acetate with final yield of 58mg/L. Using the agar well diffusion method, emodin extract doses of 0.ug/ml, 1ug/ml, 2ug/ml and 4ug/ml were tested against clinical pathogenic microorganisms. Data was analysed using SPSS 22. Results: Emodin 0.5ug/ml showed high antibacterial activity against proteus mirabilis, with growth inhibition zone of 8.7mm, followed by staphylococcus epidermidis 7mm, streptococcus pyogenes 7.6mm, staphylococcus aureus 7.5mm, escherichia coli 6.7mm and klebsiella species 0.4mm. Pseudomonas aeruginosa was resistant to emodin 0.5ug/ml. Conclusion: Emodin extract of trichoderma longibrachiatum showed high antimicrobial activity against human pathogenic bacteria.5 Keywords: Pseudomonas aeruginosa, Staphylococcus aureus, Proteus mirabilis, Escherichia coli, Trichoderma, Ethyl acetate, emodin, Agar, Mirabilis, Klebsiella, Bacterial, Polymerase.